Analisa Kepatuhan Pajak dengan Pendekatan Teori Pembelajaran Sosial Terhadap Wajib Pajak Orang Pribadi di Kab Bekasi - Agus Fuadi; Dian Sulistyorini Wulandari; Christine Yuliyanti Tiurma (Journal of Trends Economics and Accounting Research, 2023)
This study aims to determine the effect of tax knowledge, tax sanctions and the application of E-Samsat on mandatory motor vehicle compliance at the Bekasi Regency SAMSAT Office. The sample in this study were taxpayers registered at the Bekasi Regency SAMSAT Office. The sampling technique in this study used simple random sampling. The number of samples taken in the study were 100 respondents. The data collection technique used a survey method with the distribution of questionnaires. The tests in this study consisted of instrument tests, classical assumption tests and multiple linear regression analysis tests. The test was carried out using the IBM SPSS version 25 program. The test results in this study indicate that the variable knowledge of taxation and tax sanctions partially has a positive and significant effect on motor vehicle taxpayer compliance, while the implementation of E-Samsat partially has no effect on motor vehicle taxpayer compliance. at the Bekasi District SAMSAT Office. Meanwhile, simultaneously, the variables of tax knowledge, tax sanctions and the application of E-Samsat have a positive and significant effect on the compliance of motorized vehicle taxpayers at the Bekasi Regency SAMSAT Office.